Key Enzymes for Anaerobic Lactate Metabolism in Geobacter sulfurreducens - Ueki, Toshiyuki (Appl Environ Microbiol, 2021)
Growth of Geobacter sulfurreducens PCA on lactate was enhanced by laboratory adaptive evolution. The enhanced growth was considered to be attributed to increased expression of the sucCD genes, encoding a succinyl-coenzyme A (CoA) synthetase. To further investigate the function of the succinyl-CoA synthetase, the sucCD genes were deleted from G. sulfurreducens. The mutant showed defective growth on lactate but not on acetate. Introduction of the sucCD genes into the mutant restored the full potential to grow on lactate. These results verify the importance of the succinyl-CoA synthetase in growth on lactate. Genome analysis of Geobacter species identified candidate genes, GSU1623, GSU1624, and GSU1620, for lactate dehydrogenase. Deletion mutants of the identified genes for d-lactate dehydrogenase (ΔGSU1623 ΔGSU1624 mutant) or l-lactate dehydrogenase (ΔGSU1620 mutant) could not grow on d-lactate or l-lactate but could grow on acetate and l- or d-lactate, respectively. Introduction of the respective genes into the mutants allowed growth on the corresponding lactate stereoisomer. These results suggest that the identified genes were essential for d- or l-lactate utilization. The lacZ reporter assay demonstrated that the putative promoter regions were more active during growth on lactate than during growth on acetate, indicating that the genes for the lactate dehydrogenases were expressed more during growth on lactate than during growth on acetate. The gene deletion phenotypes and the expression profiles indicate that there are metabolic switches between lactate and acetate. This study advances the understanding of anaerobic lactate utilization in G. sulfurreducens. IMPORTANCE Lactate is a microbial fermentation product as well as a source of carbon and electrons for microorganisms in the environment. Furthermore, lactate is a common amendment for stimulation of microbial growth in environmental biotechnology applications. However, anaerobic metabolism of lactate has been poorly studied for environmentally relevant microorganisms. Geobacter species are found in various environments and environmental biotechnology applications. By employing genomic and genetic approaches, succinyl-CoA synthetase and lactate dehydrogenase were identified as key enzymes in anaerobic metabolism of lactate in Geobacter sulfurreducens, a representative Geobacter species. Differential gene expression during growth on lactate and acetate was observed, demonstrating that G. sulfurreducens could metabolically switch to adapt to available substrates in the environment. The findings provide new insights into basic physiology in lactate metabolism as well as cellular responses to growth conditions in the environment and can be informative for the application of lactate in environmental biotechnology.